COVID-19 Recovery Action Plan for Informal Settlements in the ECE Region - United Nations Economic Commission for Europe (United Nations, 2023)
The COVID-19 Recovery Action Plan for Informal Settlements in the UNECE Region is dealing with both – the new challenges, created by COVID-19, and the pre-existing ones, while also addressing the achievement of the Sustainable Development Goals (SDGs). This Recovery Action Plan, targeted at national and local governments in the ECE region, provides an extensive list of goals, targets, and actions that can be advanced by governments, local authorities, residents, community leaders, non-governmental organizations, and other stakeholders to help mitigate and/or prevent the COVID-19 pandemic spread. It is also designed to help build back better to achieve greater resilience against future pandemic risks while simultaneously helping to achieve the Goals of the 2030 Agenda for Sustainable Development, with a particular focus on SDG 11 on sustainable cities and human settlements.